The relationship between profitability ratio (ROE, ROA, PM and OPM) and financial performance of Mahkota Medical Centre Sdn Bhd / Suriati Selamat - Selamat, Suriati (2010)
The relationship between profitability ratio and financial performance has raised a number of questions among the academics which could becomes management system serves as a better control mechanism that may lead company to have a better in their financial performance. Measuring hospital financial performance is commonly performed by analyzing profitability of the company.Thus, the central issue that discussed in this study was focused heavily on the relationship that may exist between profitability ratio which are Return on Asset, Return on Equity, Profit Margin and Operating Profit Margin with financial performance of Mahkota Medical Centre Sdn Bhd. The paper will concentrated on Statutory Financial Statement of Mahkota Medical Centre Sdn Bhd from the period of June 2002 to June 2009. The study will be used Correlation analysis, FStatistic and T-Statistic to see the relationships between dependent and independent variables. Financial performance will be used as dependent variable and Return on Asset, Return on Equity, Profit Margin and Operating Profit Margin will be used as independent variables. According to the analysis for the year 2002 to 2009, which based on F - Statistic and Correlation Analysis found that, it is proved that there is a significant relationship exists between financial performance and profitability ratio of Mahkota Medical Centre Sdn Bhd.